The Legal Status of Cryptocurrency Assets as Inherited Property from the Perspective of Positive Law and Islamic Law in Indonesia - Bryan Fayyadh Haq Wahyudi; Kholis Roisah (Publikasi Indonesia, 2026)
The digital economy has established crypto assets as a new form of wealth, yet conventional inheritance regulations have not fully accommodated their digital characteristics. This study aims to analyze the legal standing of crypto assets as inheritance objects under the Civil Code and Islamic Law, as well as their distribution mechanisms. The research employs a normative juridical method using statutory and conceptual approaches. The findings reveal that crypto assets are legally classified as intangible movable property under the Civil Code and qualify as m?l (wealth) eligible for inheritance under Islamic Law, provided they possess clear economic value and utility. However, technical constraints related to private key confidentiality and extreme value volatility remain primary obstacles in their distribution process. The study concludes that while crypto assets have a solid legal foundation to be recognized as inheritable property in Indonesia, sectoral regulatory harmonization and the development of digital will instruments are essential to ensure legal certainty and protect heirs’ economic rights over decentralized digital assets. Furthermore, the valuation of crypto assets for inheritance purposes should ideally be conducted at the time of distribution rather than at the time of the testator’s death, or alternatively through direct transfer of asset units, to uphold the principle of justice and safeguard heirs’ absolute rights amid the extreme price volatility characteristic of these digital assets.